Effective Approaches to Spanish Language Teaching in Afghanistan - Walizada Sara, Gul Ghotai (International journal of multicultural and multireligious understanding, 2025)
Spanish language instruction has seen a marked increase in Afghanistan, particularly in higher education and within the framework of cultural exchange initiatives. In a context defined by both multilingualism and multiculturalism, the development and application of effective, modern pedagogical strategies is essential to address the specific needs of Afghan learners. This research examines proven methodologies for teaching contemporary Spanish in Afghanistan, emphasizing communicative approaches, task-based instruction, technology integration, hybrid pedagogical models, and cultural content. The analysis considers both the strengths and limitations of each method, taking into account constraints such as limited resources and minimal contact with native speakers. Findings indicate that blending innovative teaching practices with individualized support and culturally immersive experiences fosters greater motivation, sustained engagement, and higher levels of communicative competence among students. Such strategies are particularly pertinent where Spanish is considered a non-traditional foreign language and language learning is closely connected to academic, professional, or migratory goals.